The use of food delivery applications among different consumer groups in the Czech Republic - Al Frouh, Yasmeen (2022)
This Bachelor thesis aims to evaluate the perspective of consumers based in the Czech Republic on food delivery applications. More specifically, to conduct a qualitative research to investigate the influence of different attributes of an application on the interviewees. Furthermore, to provide a comparison of application characteristics that have an impact on interviewees’ evaluation of the service and characteristics that have the greatest impact on the final consumer’s ordering decision. The method used to conduct this research, is an in-depth interview. The interviews consisted of 15 participants residing in the Czech Republic with different demographics (Age, Gender, Income, Education). Participants were invited to share their perceptions in order to explore the topic. Results derived from the study showed delivery tracking, food images, trust, design, and brand packaging all play a role in the perception and evaluation of food delivery applications however promotions and discounts, delivery time and fee, user-friendliness, and customer service have the greatest impact on the final consumer’s ordering decision. Apart from these findings, there are several observations such that Bolt is the most preferred application. These observations as well as findings from research pave the way for more extensive qualitative research of this phenomenon.